Fabrication and characterization of Ag‐ and Ga‐doped mesoporous glass‐coated scaffolds based on natural marine sponges with improved mechanical properties. Issue 8 (6th November 2020) - Ciraldo, Francesca E.; Arango‐Ospina, Marcela; Goldmann, Wolfgang H.; Beltrán, Ana M.; Detsch, Rainer; Gruenewald, Alina; Roether, J. A.; Boccaccini, Aldo R.
Abstract: Natural marine sponges were used as sacrificial template for the fabrication of bioactive glass‐based scaffolds. After sintering at 1050°C, the resulting samples were additionally coated with a silicate solution containing biologically active ions (Ag and Ga), well‐known for their antibacterial properties. The produced scaffolds were characterized by superior mechanical properties (maximum compressive strength of 4 MPa) and total porosity of ~80% in comparison to standard scaffolds made by using PU foam templates. Direct cell culture tests performed on the uncoated and coated samples showed positive results in terms of adhesion, proliferation, and differentiation of MC3T3‐E1 cells. Moreover, vascular endothelial growth factor (VEGF) secretion from cells in contact with scaffold dissolution products was measured after 7 and 10 days of incubation, showing promising angiogenic results for bone tissue engineering applications. The antibacterial potential of the produced samples was assessed by performing agar diffusion tests against both Gram‐positive and Gram‐negative bacteria.